TaMYB-CC5 gene specifically expressed in root improve tolerance of phosphorus deficiency and drought stress in wheat - Zheng, Lei (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.